Online training module for micro suturing incorporating motor imagery and mental practice: a design and development research study. Issue 9 (17th May 2022) - Rajaratnam, Vaikunthan; Ng, Hannah Jia Hui; Rahman, Norana Abdul; Dong, Chaoyan
Abstract: Introduction: There have been reduced opportunities for surgical skill acquisition due to the COVID‐19 pandemic and the regulated training hours. Despite these challenges, self‐regulated learning allows trainees to learn continuously, and one form of this is through mental practice and motor imagery. The study aimed to design and develop an online basic micro suturing training module for skill acquisition for self‐regulated learning using a low‐fidelity rubber glove model. Methods: This study utilized a design and developmental research framework and Mayer's multimedia theory guidelines. The primary author created an online instructional module on micro suturing based on the ADDIE instructional design model. This module was then evaluated in a pilot study comparing the new training model to traditional methods of learning using an experimental design. Results: This study describes the use of Design and Development Research to create a new model for surgical skill training and a tool for producing instructional materials and learning products for online learning. The product was evaluated using an experimental design and showed a significant effect on the quality of motor skill outcome and the richness of motor imagery using the resource developed in the research. Conclusion: This study describes the methodological approach of a design and developmental framework to create an online training module for micro suturing which has significant utility in hand surgery. Abstract : This study describes the methodological approach of a design and developmental framework to create an online training module for micro suturing which has significant utility in hand surgery.